Severe and persistent facial nerve stimulation after cochlear implantation in a patient with cochlear–facial dehiscence: a case report - Jingyuan Chen (SAGE Publishing, 2021)
Generally, cochlear implants (CIs) are effective in helping patients improve their hearing performance; however, some patients have poor hearing performance owing to facial nerve stimulation (FNS), which is often associated with cochlear anomalies. We report a case with a normal cochlea and severe and persistent FNS owing to cochlear–facial dehiscence (CFD) that affected the CI outcomes. Preoperatively, a careful review of the computed tomography images before CI surgery is necessary not only for patients with otosclerosis and inner ear malformations but also for patients with normal cochlear structures because facial nerve anomalies could be present.